Observational fear learning involves affective pain system and Ca(v)1.2 Ca2+ channels in ACC - Jeon, Daejong; Kim, Sangwoo; Chetana, Mattu; Jo, Daewoong; Ruley, H. Earl; Lin, Shih-Yao; Rabah, Dania; Kinet, Jean-Pierre; Shin, Hee-Sup (NATURE PUBLISHING GROUP, 2010)
Fear can be acquired vicariously through social observation of others suffering from aversive stimuli. We found that mice (observers) developed freezing behavior by observing other mice (demonstrators) receive repetitive foot shocks. Observers had higher fear responses when demonstrators were socially related to themselves, such as siblings or mating partners. Inactivation of anterior cingulate cortex (ACC) and parafascicular or mediodorsal thalamic nuclei, which comprise the medial pain system representing pain affection, substantially impaired this observational fear learning, whereas inactivation of sensory thalamic nuclei had no effect. The ACC neuronal activities were increased and synchronized with those of the lateral amygdala at theta rhythm frequency during this learning. Furthermore, an ACC-limited deletion of Ca(v)1.2 Ca2+ channels in mice impaired observational fear learning and reduced behavioral pain responses. These results demonstrate the functional involvement of the affective pain system and Ca(v)1.2 channels of the ACC in observational social fear.
Keywords: ANTERIOR CINGULATE CORTEX; PHASE SYNCHRONIZATION; WORKING-MEMORY; AMYGDALA; EMPATHY; BEHAVIOR; OTHERS; GENE; MICE; NEUROSCIENCE